MENIMBANG PEMIKIRAN MASDAR FARID MASUDI TENTANG DOUBLE TAXS (ZAKAT DAN PAJAK) - Hidayat, Taufiq (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2013)
The revenue sources of CountryÂ in the early days of Islam, such as zakat and taxes they are jizyah, kharaj, max (customs), and usyr (export-import customs) and also ghanimah and fai (spoils of war and confiscated items). For Muslims in Indonesia,in addition they have to pay taxes to the state that include property tax,commercial goods tax, goods consumption tax, fiscal when traveling abroad, income tax, etc., they also have to pay zakat that include zakat fitrah and zakat property. Thus, Indonesian Muslims have to bear double taxs, they are taxation and zakat. This academic anxiety felt by one of the Indonesian Muslim intellectual, Masdar Farid Masudi. Departing from that academic anxiety Masdar then pour his fresh ideas and even controversial, especially on the issue of double taxs.